2019
DOI: 10.3844/ajisp.2019.10.18
|View full text |Cite
|
Sign up to set email alerts
|

The Role of SLC22A4 Gene Polymorphisms in the Response to Salbutamol in Asthmatic Patients

Abstract: Response to Bronchodilators is influenced by many factors including genetics. To evaluate the influence of SLC22A4 gene polymorphisms (rs3792876 and rs2073838) on the response to inhaled salbutamol in asthmatic patients, bronchodilator response was assessed in 180 bronchial asthma patients via measuring changes of the Forced Expiratory Volume in one second (FEV1) after the administration of inhaled salbutamol and genotyping for rs3792876 and rs2073838 was carried out using real-time polymerase chain reaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…OCTN1 has been implicated in the uptake and altered metformin plasma concentration in OCTN1 L503F genetic variants [5,7]. A study has recently reported the impact of rs3792876 homozygous genotype in the improved clinical efficacy of inhaled salbutamol suggesting the role of OCTN1 in drug absorption [17]. Our results showed a lack of significant association of OCTN1 rs1050152 and rs3792876 genotypes on the clinical efficacy of gabapentinoids between nonresponders and responders (P = 0.718 and 0.314, respectively).…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…OCTN1 has been implicated in the uptake and altered metformin plasma concentration in OCTN1 L503F genetic variants [5,7]. A study has recently reported the impact of rs3792876 homozygous genotype in the improved clinical efficacy of inhaled salbutamol suggesting the role of OCTN1 in drug absorption [17]. Our results showed a lack of significant association of OCTN1 rs1050152 and rs3792876 genotypes on the clinical efficacy of gabapentinoids between nonresponders and responders (P = 0.718 and 0.314, respectively).…”
Section: Discussioncontrasting
confidence: 60%
“…The main factors for nonadherence to the treatment were poor efficacy and tolerability of pregabalin [20]; however, the role of genetic variations of the transporters in relation to the therapeutic efficacy of the substrate drugs needs to be explored. The pharmacological and pathophysiological roles of common genetic variants of SLC22A4 OCTN1 rs1050152 and rs3792876 in the absorption and disposition of various drugs and autoimmune and inflammatory diseases have been reported in different studies [4][5][6][7][8][9]17]. The influence of the OCTN1 genetic variants on the uptake and clearance of substrate drugs might result in variable clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation